Revolusi Digital dalam Pendidikan Islam Meningkatkan Kualitas Pembelajaran Melalui Integrasi Teknologi - Devintya Putriana; Adinda Qurrotul Aini; Akmal Irsyad; Mu’alimin Mu’alimin (Reflection : Islamic Education Journal, 2024)
This research explores how the integration of technology in Islamic teaching affects the quality of learning. Using a qualitative approach through literature study, this research analyzes five articles from various sources to explore the challenges and opportunities faced by teachers in using technology. It was found that although the use of technology is growing, many teachers face difficulties in using technology effectively due to a lack of training and support. This research emphasizes the need for comprehensive training programs to improve teachers' skills in using digital tools to create more interactive and innovative learning environments. The impact of these findings can be very significant for enriching Islamic education strategies that are more appropriate in the current digital era.